Uncovering biomarkers during therapeutic neuromodulation with PARRM: Period-based Artifact Reconstruction and Removal Method - Evan M. Dastin-van Rijn; Nicole R. Provenza; Jonathan S. Calvert; Ro'ee Gilron; Anusha B. Allawala; Radu Darie; Sohail Syed; Evan Matteson; Gregory S. Vogt; Michelle Avendano-Ortega; Ana C. Vasquez; Nithya Ramakrishnan; et al. (Cell Reports: Methods, 2021)
Summary: Advances in therapeutic neuromodulation devices have enabled concurrent stimulation and electrophysiology in the central nervous system. However, stimulation artifacts often obscure the sensed underlying neural activity. Here, we develop a method, termed Period-based Artifact Reconstruction and Removal Method (PARRM), to remove stimulation artifacts from neural recordings by leveraging the exact period of stimulation to construct and subtract a high-fidelity template of the artifact. Benchtop saline experiments, computational simulations, five unique in vivo paradigms across animal and human studies, and an obscured movement biomarker are used for validation. Performance is found to exceed that of state-of-the-art filters in recovering complex signals without introducing contamination. PARRM has several advantages: (1) it is superior in signal recovery; (2) it is easily adaptable to several neurostimulation paradigms; and (3) it has low complexity for future on-device implementation. Real-time artifact removal via PARRM will enable unbiased exploration and detection of neural biomarkers to enhance efficacy of closed-loop therapies. Motivation: Electrophysiological recordings concurrent with electrical stimulation of the brain and spinal cord are often corrupted by stimulation artifact. The removal of stimulation artifact is a necessary step toward identifying neural biomarkers that can be consistently used to titrate neuromodulation therapies or discover the underlying disease neuropathology. Thus, we developed a Period-based Artifact Reconstruction and Removal Method (PARRM) to provide a solution to removing such artifacts from low- and high-sample-rate recordings. PARRM is adaptive to changes in artifact shape, is robust to aliasing, and has low computational overhead readily implementable for use in real time. Our method aims to enable the investigation, and eventual development, of closed-loop neuromodulation therapies.